Locus of Control and Its Intergenerational Implications for Early Childhood Skill Formation - Warn N. Lekfuangfu; Francesca Cornaglia; Nattavudh Powdthavee; Nele Warrinnier (Institute for the Study of Labor (IZA), 2014)
We propose a model in which parents have a subjective belief about the impact of their investment on the early skill formation of their children. This subjective belief is determined in part by locus of control (LOC), i.e., the extent to which individuals believe that their actions can influence future outcomes. Consistent with the theory, we show that maternal LOC measured at the 12th week of gestation strongly predicts early and late child cognitive and noncognitive outcomes. We also utilize the variation in maternal LOC to help improve the specification typically used in the estimation of skill production function parameters.
Keywords: J01; I31; 330; locus of control; parental investment; human capital accumulation; early skill formation; ALSPAC